REINTERPRETASI MA'NA QITAL DENGAN PENDEKATAN MA'NA CUM MAGZA - Faiqotul Mala (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
The problem of terrorism raises concerns and unrest that never ends. Terrorism acts are still a potential threat to national security stability, so it demands the government's vigilance to prevent and overcome them. One of the factors causing the difficulty of overcoming the problem of terrorism is ideological differences and understanding of religious teachings or interpretations of qital verses that are less precise. On the other hand, differences in the method of interpreting a verse from various groups also color the pattern of people's understanding of Islam. Therefore, this article tries to reinterpret the understanding of the qital verse which has been used as a legitimacy to justify acts of terror. Of the many qital verses contained in the Qur'an, this article only focuses on the interpretation of Surah al-Baqoroh verses 190 and 191. By using the ma'na cum magza approach in interpreting and understanding these verses, it will be proven how far the theory goes. ma'na cum maghza can be an alternative interpretation methodology that leads to a relevant understanding. The theory promoted by Sahiron sets an operational step which includes linguistic analysis first, then historical analysis (historical analysis) and then develops the significance of the verse according to with the current situation.